Intervention in Yemen in 2015: assessing the alleged violations of international humanitarian law by Saudi-Led coalition in Yemen conflict - Gesins, Aleksandrs (Riga Graduate School of Law, 2020)
Importance of international humanitarian law has emerged significantly in last two decades, becoming as the primary legal source, which is used as the pre-emptive measure of restricting international actors from indiscriminate actions and use of prohibited weapons with regulating the entire conduct of war. Saudi-led intervention in Yemen has become a vivid example of how the well-established legal rules can become irrelevant, because of the wrong approach, that was taken by respective parties to serve its political interests, while neglecting its legal obligations. Despite the emerged conflict of interests between the law and politics, International Humanitarian Law concerning Yemen conflict has remained as the supreme legal framework that can explain unlawfulness of conducted violations of the acting party. The paper discusses the applicability of International Humanitarian Law in the case of Yemen, especially the nature of alleged violations, by determining unlawfulness of conducted actions
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International humanitarian law; Yemen